MODELING THE PRODUCTION PROCESS USING IDEF0 WITH A CASE STUDY OF AUTOMOTIVE GLASS COMPANIES - Fahriza Nurul Azizah (Universitas Harapan Medan, 2019)
One of the uses of IDEF0 is for modeling. This research makes modeling in the production process in the manufacturing industry, the automotive glass company. This company produces safety glass which is one component that is assembled in a car. The research aims to provide information about the use and understanding obtained from modeling using IDEF0. The results of the research show that the process of drawing the production process model which consists of cutting, printing, tempering and assembling is more comprehensive and clear. IDEF0 has provided an understanding of the production process, input, output, mechanism and control as well as more detailed and structured activities more easily.